Anatomical Relationships of Burch Colposuspension Sutures. Issue 2 (March 2017) - Kinman, Casey L.; Agrawal, Anubhav; Deveneau, Nicolette E.; Meriwether, Kate V.; Herring, Nicole R.; Francis, Sean L.
Abstract : Objectives: The prevalent use of minimally invasive midurethral slings for the treatment of stress urinary incontinence in the last several decades has resulted in fewer Burch procedures being performed and diminished surgical experience in performing the Burch colposuspension. However, recent antimesh media has resulted in more patients requesting nonmesh anti-incontinence procedures and a subsequent need for surgeons to refamiliarize themselves with the Burch procedure and its relevant anatomy. The objective of this study was to evaluate the relationships of Burch sutures to surrounding neurovascular anatomic structures in the human cadaver. Methods: The retropubic space of 11 unembalmed female cadavers was dissected, and a Burch procedure performed. The distance from the Burch sutures' location through both Cooper's ligament and the vagina to the obturator neurovascular bundle and external iliac vessels was measured. Results: The mean distance from the most lateral stitch in Cooper's ligament to the obturator bundle was 25.9 ± 7.6 mm and to the external iliac vessels was 28.9 ± 9.3 mm, and in some instances, these structures were less than 1.5 cm away. Conclusions: The obturator bundle and external iliac lie, on average, within 3 cm of sutures placed during a Burch colposuspension. Knowledge of these anatomical relationships is valuable when dissecting the space of Retzius and placing sutures for a Burch to avoid injury. Abstract : Sutures placed when performing a Burch colposuspension in female cadavers were found to lie within 3 cm of the obturator bundle and external iliac vessels.